Functional ankle instability as a risk factor for osteoarthritis: using T2-mapping to analyze early cartilage degeneration in the ankle joint of young athletes - Golditz, Tobias C.; Steib, Simon; Pfeifer, K.; Uder, M.; Gelse, K.; Janka, R.; Hennig, F. F.; Welsch, G. H. (Osteoarthritis and cartilage, 2014)
Objective - The aim of this study was to investigate, using T2-mapping, the impact of functional instability in the ankle joint on the development of early cartilage damage. - Methods - Ethical approval for this study was provided. Thirty-six volunteers from the university sports program were divided into three groups according to their ankle status: functional ankle instability (FAI, initial ankle sprain with residual instability); ankle sprain Copers (initial sprain, without residual instability); and controls (without a history of ankle injuries). Quantitative T2-mapping magnetic resonance imaging (MRI) was performed at the beginning (‘early-unloading’) and at the end (‘late-unloading’) of the MR-examination, with a mean time span of 27 min. Zonal region-of-interest T2-mapping was performed on the talar and tibial cartilage in the deep and superficial layers. The inter-group comparisons of T2-values were analyzed using paired and unpaired t-tests. Statistical analysis of variance was performed. - Results - T2-values showed significant to highly significant differences in 11 of 12 regions throughout the groups. In early-unloading, the FAI-group showed a significant increase in quantitative T2-values in the medial, talar regions (P = 0.008, P = 0.027), whereas the Coper-group showed this enhancement in the central-lateral regions (P = 0.05). Especially the comparison of early-loading to late-unloading values revealed significantly decreasing T2-values over time laterally and significantly increasing T2-values medially in the FAI-group, which were not present in the Coper- or control-group. - Conclusion - Functional instability causes unbalanced loading in the ankle joint, resulting in cartilage alterations as assessed by quantitative T2-mapping. This approach can visualize and localize early cartilage abnormalities, possibly enabling specific treatment options to prevent osteoarthritis in young athletes.
Gesehen am 15.09.2023